Measuring hydrological connectivity inside a soil by low field nuclear magnetic resonance relaxometry. Issue 1 (11th December 2017) - Conte, Pellegrino; Ferro, Vito
Abstract: Hydrological connectivity inside the soil is related to the spatial patterns inside the soil (i.e., the structural connectivity). This, in turn, is directly associated with the physical and the chemical processes at a molecular level (i.e., the functional connectivity). Nuclear magnetic resonance (NMR) relaxometry can be successfully applied to reveal both structural and functional components of soil hydrological connectivity. In the present study, the low field NMR relaxometry was applied on water suspended soils sampled at the upstream‐ and downstream‐end of three different length plots. Also the sediments collected from the storage tanks at the end of each plot were water suspended and monitored by NMR relaxometry. The results from the NMR investigations were elaborated by using a mathematical approach in order to quantify both the functional and structural connectivity components. In particular, following integration of the T 1 distribution curve, an S‐shaped curve was obtained. It revealed two plateaus corresponding to the shortest ( low component ) and the longest ( high component ) intervals of relaxation times, respectively. According to relaxometry theory, the two T 1 intervals, associated to the different plateaus, were attributed to micro and macro soil pores, respectively. The two T 1 intervals were used to define a functional connectivity index, while the central part of the S‐shaped distribution was used to define a structural connectivity index. Here we provide the physical meaning of the our mathematical approach, thereby revealing that functional connectivity index increases with plot length, as a result of a selective eroded particle transport. Moreover, the relationship structural connectivity index versus plot length resulted quasi‐independent of grainsize distribution, whereas the values of the structural connectivity index for the sediment samples resulted lower than those obtained for the corresponding soils.